The Intra-Industry Effects of Going-Private Transactions. - Bendeck, Yvette M; Slovin, Myron B; Sushka, Marie E (Journal of Finance, 1991)
The authors demonstrate that bids to take firms private generate significantly positive valuation effects for industry rivals of target firms. These valuation effects cannot reflect either synergy or monopoly since no consolidation of operating firms is involved in such transactions. Participation by buyout specialists in the bid does not significantly affect these gains. Bids by outsiders and bids by incumbent managers generate similar valuation effects for industry rivals. The effect on share prices of industry rivals is inversely related to the capitalized values of rival firms relative to the target firm. The authors also report valuation effects for target firms.